2006
DOI: 10.1111/j.0021-9029.2006.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Stereotypes: New Challenges in a Changing Workplace and Workforce

Abstract: The current research investigated age and gender stereotypes in relation to adaptive performance. Using methods similar to those used in Schein's studies (1973, 1975), 496 undergraduate students rated 1 of 7 targets on 6 dimensions of adaptive performance. All of the targets varied in age (25, 40, or 55 years) and gender, except one that was age and gender neutral. The 7 th served as a reference group and was an age-and gender-neutral target. Results showed that older targets were perceived as less adaptable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 72 publications
2
39
1
3
Order By: Relevance
“…Conversely, they are positively valued on their warmth: Elderly are perceived as friendly, sincere, and warm (Cuddy & Fiske, 2002;Cuddy, Norton, & Fiske, 2005). Research on stereotypes about older individuals in the workplace has supported mixed content of age-related stereotypes (Chiu, Chan, Snape, & Redman, 2001;DeArmond et al, 2006;Finkelstein & Farrell, 2007;McCann & Giles, 2002;Shore & Goldberg, 2005). Like for retirees, older workers' warmth is positively valued in the workplace: Older workers are perceived as more reliable (Metcalf & Thompson, 1990) and as having better interpersonal skill (Rosen & Jerdee, 1976) than younger workers.…”
Section: Stereotypes About Older Workersmentioning
confidence: 99%
“…Conversely, they are positively valued on their warmth: Elderly are perceived as friendly, sincere, and warm (Cuddy & Fiske, 2002;Cuddy, Norton, & Fiske, 2005). Research on stereotypes about older individuals in the workplace has supported mixed content of age-related stereotypes (Chiu, Chan, Snape, & Redman, 2001;DeArmond et al, 2006;Finkelstein & Farrell, 2007;McCann & Giles, 2002;Shore & Goldberg, 2005). Like for retirees, older workers' warmth is positively valued in the workplace: Older workers are perceived as more reliable (Metcalf & Thompson, 1990) and as having better interpersonal skill (Rosen & Jerdee, 1976) than younger workers.…”
Section: Stereotypes About Older Workersmentioning
confidence: 99%
“…Mostly, if the allocation of jobs is ordered primarily by institutional characteristics rather than the qualities of the people that hold particular roles, and if these characteristics are controlled by employers through the hours, conditions and remuneration they offer to potential employees, and then labor market interventions will need to target employers' recruitment practices. Several studies revealed the discrimination and stereotypes of employees based on age reason [1][2][3][4][5][6][7]. It was found that the managers' attitudes and stereotypes can be either negative or positive stereotypes towards older employees [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many stereotypes pronounced negative characteristics about older employees [1,5] such as older employees were less flexible [9,10], less productivity [3,11], less motivated [5], less healthy and susceptible to illness [12], less adaptable to changes [1], problems accepting new technology [9] and less trainable [13] as compared to younger employees. Notably, older employees seem to be undervalued in corporate environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that find differences in ratings of older men and women show that women rate older persons more favorably in general (Bodner et al 2012;DeArmond et al 2006;Deutsch et al 1986), some find that this applies only for the ratings of older women (Laditka et al 2004), and yet others do not find any gender differences at all (Grant et al 2002). We therefore do not have any specific hypotheses for the interaction of participant and target gender.…”
Section: Introductionmentioning
confidence: 99%